KEEFEKTIFAN PELAKSANAAN PROGRAM UPAYA KHUSUS KOMODITAS JAGUNG DI KABUPATEN KETAPANG - Heristi, Veny; Sudrajat, Jajat; Gafur, Sutarman (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2021)
The effectiveness of the Upsus Program on the national agenda is needed further evaluation on several areas. This study aims to analyze the effectiveness on implementation of the Upsus Program on development of corn commodity in Sungai Melayu Rayak District, Ketapang Regency and the participants’ agricultural products productivity before and after the program. A Survey Method is conducted in this case study by interviewing 40 farmers who participated in the program from four villages. The results showed the process of implementing the program cycle and the use of assistance that had been achived was quite good. Other success indicators could be seen from the socialisazation that reached out most of the the farmers, increased planting area, and an increase in productivity. A weakness was found from the lack of precise implementation during the program which impacted on the planting schedule.